Minat Penanaman Modal Dalam Negeri Dan Penanaman Modal Asing Di Jawa Barat Serta Faktor Yang Mempengaruhinya - Nisrina Salsabila; Sabina Putri Damayanti Nasution; Salma Habiba Sabrine; Fachrul Hanif Rumasukun (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This journal examines investment trends in West Java Indonesia and its influencing factors, with a focus on domestic (PMDN) and foreign direct investment (FDI). This study uses a secondary data analysis approach based on PMDN and PMA investment and then generalizes to understand the factors that influence investment decisions. Analysis of PMDN investment data from 2006 to 2023 shows a significant and consistent increasing trend, reaching a peak of IDR 88,021.9 billion in 2023. In contrast, foreign investment (FDI) shows a fluctuating trend but shows stability and gradual growth overall, especially after 2013.